The Heisenberg antiferromagnet on the square-kagomé lattice - Richter, J.; Schulenburg, J.; Tomczak, P.; Schmalfuß, D. (Condensed Matter Physics, 2009)
We discuss the ground state, the low-lying excitations as well as high-field thermodynamics of the Heisenberg
antiferromagnet on the two-dimensional square-kagom´e lattice. This magnetic system belongs to the class
of highly frustrated spin systems with an infinite non-trivial degeneracy of the classical ground state as it is
also known for the Heisenberg antiferromagnet on the kagom´e and on the star lattice. The quantum ground
state of the spin-half system is a quantum paramagnet with a finite spin gap and with a large number of
non-magnetic excitations within this gap. We also discuss the magnetization versus field curve that shows a
plateaux as well as a macroscopic magnetization jump to saturation due to independent localized magnon
states. These localized states are highly degenerate and lead to interesting features in the low-temperature
thermodynamics at high magnetic fields such as an additional low-temperature peak in the specific heat and
an enhanced magnetocaloric effect. Ми обговорюємо основний стан, низьколежачi збудження, а також термодинамiку у сильному полi антиферомагнетика Гайзенберга на двовимiрнiй ґратцi квадратне кагоме. Ця магнiтна система належить до класу сильно фрустрованих спiнових систем з безмежним нетривiальним виродженням класичного основного стану, так само, як i антиферомагнетик Гайзенберга на ґратцi кагоме i на ґратцi зiрка. Квантовий основний стан спiн-половина системи є квантовим парамагнетиком iз скiнченою спiновою щiлиною та великим числом немагнiтних збуджень всерединi щiлини. Ми також обговорюємо криву намагнiченiсть-поле, у якiй є плато та макроскопiчний стрибок намагнiченостi до значення насичення через стани, що називаються незалежними локалiзованими магнонами. Цi локалiзованi стани є сильно виродженими та зумовлюють цiкавi риси низькотемпературної термодинамiки у сильному магнiтному полi, такi як додатковий низькотемпературний пiк у теплоємностi i посилений магнiтокалоричний ефект.